2023
DOI: 10.2174/1570161121666230208130349
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Distinctive Mechanism of Shenqi Compound in Treating Rats with Type 2 Diabetes Mellitus by Comparing with Metformin

Abstract: background: In China, The traditional Chinese medicine (TCM) has been employed in Type 2 diabetes mellitus (T2DM) treatment for centuries and need furher elucidating the mechanisms of action. method: To investigate how the TCM ShenQi (SQC) formulation differs from metformin, four rat groups, including control, model, T2DM rats treated using SQC (SQC group), and T2DM rats treated using metformin (Met group), were constructed. The differentially expressed genes (DEGs) between SQC and metformin groups were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Long-term clinical experience in China has illuminated SQC’s potential as a candidate drug for mitigating DVC (Hao et al 2017 ; Wang et al 2018a ). Observations from diverse patient populations have suggested that SQC’s administration is associated with reduced vascular calcification and improved overall vascular health (Yang et al 2023a ; Fu et al 2023 ). However, to translate these observations into robust therapeutic strategies, a deeper exploration of SQC’s specific effects and underlying mechanisms is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term clinical experience in China has illuminated SQC’s potential as a candidate drug for mitigating DVC (Hao et al 2017 ; Wang et al 2018a ). Observations from diverse patient populations have suggested that SQC’s administration is associated with reduced vascular calcification and improved overall vascular health (Yang et al 2023a ; Fu et al 2023 ). However, to translate these observations into robust therapeutic strategies, a deeper exploration of SQC’s specific effects and underlying mechanisms is indispensable.…”
Section: Introductionmentioning
confidence: 99%